2019
DOI: 10.1039/c9nr00806c
|View full text |Cite
|
Sign up to set email alerts
|

Reversible gas–solid reaction in an electronically-stimulated palladium nanogap

Abstract: A reversible gas–solid reaction occurs on the tip surface of a positively biased palladium electrode in nitrogen in ETEM apparatus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The catalytic reaction is considered to be triggered by the random collision of reactive gas molecules with the catalyst surface. Here we visualize the progressive change in the atomic structure of a metal surface in an ambient environment by applying in situ transmission electron microscopy (TEM) under a strong electrostatic field . The elemental excitation behind the observed phenomena is extremely fast electron tunneling that activates oxygen gas molecules for 10 −15 s (fs) to 10 −18 s (as) .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The catalytic reaction is considered to be triggered by the random collision of reactive gas molecules with the catalyst surface. Here we visualize the progressive change in the atomic structure of a metal surface in an ambient environment by applying in situ transmission electron microscopy (TEM) under a strong electrostatic field . The elemental excitation behind the observed phenomena is extremely fast electron tunneling that activates oxygen gas molecules for 10 −15 s (fs) to 10 −18 s (as) .…”
Section: Figurementioning
confidence: 99%
“…[10][11][12][13] The catalytic reaction is considered to be triggered by the random collision of reactive gas molecules with the catalyst surface.H ere we visualize the progressive change in the atomic structure of am etal surface in an ambient environment by applying in situ transmission electron microscopy (TEM) under as trong electrostatic field. [14,15] Thee lemental excitation behind the observed phenomena is extremely fast electron tunneling [16] that activates oxygen gas molecules for 10 À15 s( fs) to 10 À18 s( as). [2] Thed irect visualization, made possible for the first time in this study,p rovides us with ac rucial starting point to understand the electronic and thermic effects to progressively change the atomic structure by catalytic chemical, surface chemical, electrochemical, and biochemical reactions in the nanometer dimension and in an ambient environment.…”
mentioning
confidence: 99%
“…We have investigated atomic structures and dynamics of nanomaterials under reaction conditions by ETEM while taking into account the effects of electron irradiation [2][3][4][5][6][7]. We have found that the surface of Pt nanoparticles is oxidized in O2 gas under electron irradiation ( Figure 1).…”
mentioning
confidence: 99%
“…Figure 2. A PdN nanostructure formed on the surface of the positive Pd electrode in an electrically-biased nanogap with N2 gas [6]. The biasing voltage between the electrodes,is (a) 0 V and (b) 8.0 V.…”
mentioning
confidence: 99%
See 1 more Smart Citation